Evaluation of Antiproliferative Properties of CoMnZn-Fe2O4 Ferrite Nanoparticles in Colorectal Cancer Cells - Venkatesha Narayanaswamy; Bilal Rah; Imaddin A. Al-Omari; Alexander S. Kamzin; Hafsa Khurshid; Jibran Sualeh Muhammad; Ihab M. Obaidat; Bashar Issa (MDPI AG, 2024)
The PEG-coated ferrite nanoparticles Co0.2Mn0.6Zn0.2Fe2O4 (X1), Co0.4Mn0.4Zn0.2Fe2O4 (X2), and Co0.6Mn0.2Zn0.2Fe2O4 (X3) were synthesized by the coprecipitation method. The nanoparticles were characterized by XRD, Raman, VSM, XPS, and TEM. The magnetic hyperthermia efficiency (MH) was determined for PEG-coated nanoparticles using an alternating magnetic field (AMF). X2 nanoparticles displayed the highest saturation magnetization and specific absorption rate (SAR) value of 245.2 W/g for 2 mg/mL in a water medium. Based on these properties, X2 nanoparticles were further evaluated for antiproliferative activity against HCT116 cells at an AMF of 495.25 kHz frequency and 350 G strength, using MTT, colony formation, wound healing assays, and flow cytometry analysis for determining the cell viability, clonogenic property, cell migration ability, and cell death of HCT116 cells upon AMF treatment in HCT116 cells, respectively. We observed a significant inhibition of cell viability (2% for untreated control vs. 50% for AMF), colony-forming ability (530 cells/colony for untreated control vs. 220 cells/colony for AMF), abrogation of cell migration (100% wound closure for untreated control vs. 5% wound closure for AMF), and induction of apoptosis-mediated cell death (7.5% for untreated control vs. 24.7% for AMF) of HCT116 cells with respect to untreated control cells after AMF treatment. Collectively, these results demonstrated that the PEG-coated (CoMnZn-Fe2O4) mixed ferrite nanoparticles upon treatment with AMF induced a significant antiproliferative effect on HCT116 cells compared with the untreated cells, indicating the promising antiproliferative potential of the Co0.4Mn0.4Zn0.2Fe2O4 nanoparticles for targeting colorectal cancer cells. Additionally, these results provide appealing evidence that ferrite-based nanoparticles using MH could act as potential anticancer agents and need further evaluation in preclinical models in future studies against colorectal and other cancers.